2010
DOI: 10.3758/mc.38.6.809
|View full text |Cite
|
Sign up to set email alerts
|

Component processes underlying future thinking

Abstract: This study sought to investigate the component processes underlying the ability to imagine future events, using an individual-differences approach. Participants completed several tasks assessing different aspects of future thinking (i.e., fluency, specificity, amount of episodic details, phenomenology) and were also assessed with tasks and questionnaires measuring various component processes that have been hypothesized to support future thinking (i.e., executive processes, visual-spatial processing, relational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
120
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 55 publications
12
120
1
Order By: Relevance
“…The role of personal relevance in autonoetic experience is also suggested by studies showing that the degree to which people report feelings of pre-experience and mental time travel when imagining future events is related to individual differences in future time perspective (i.e., a general concern for the future, including a focus on planning and future goals; Arnold, McDermott, & Szpunar, 2011b) and self-consciousness (i.e., the tendency to think about one 's beliefs, aspirations, and values;D'Argembeau, Ortoleva, Jumentier, & Van der Linden, 2010).…”
mentioning
confidence: 91%
“…The role of personal relevance in autonoetic experience is also suggested by studies showing that the degree to which people report feelings of pre-experience and mental time travel when imagining future events is related to individual differences in future time perspective (i.e., a general concern for the future, including a focus on planning and future goals; Arnold, McDermott, & Szpunar, 2011b) and self-consciousness (i.e., the tendency to think about one 's beliefs, aspirations, and values;D'Argembeau, Ortoleva, Jumentier, & Van der Linden, 2010).…”
mentioning
confidence: 91%
“…D'Argembeau et al [25] examined in young adults the contribution of some executive function (verbal and semantic fluency) and working memory (measured with the letter-number sequencing task taken from WAIS III, [27]) tasks to different dimension of episodic future thinking performance, i.e., fluency (e.g., how many unique future events can a person generate in 1 min), specificity (e.g., whether a person can construct a unique potential future event), and details (e.g., how many specific episodic details can a person produce about a possible future event). D'Argembeau et al [25] reported that the factor representing executive processes was the only independent predictor of autobiographical fluency, autobiographical specificity, and the amount of episodic details.…”
Section: Introductionmentioning
confidence: 98%
“…For example, it has been demonstrated, in young adults, that executive processes may support the strategic aspects of retrieving autobiographical details [24] and recombining them into future scenarios [25]. Among the various executive processes, Suddendorf and Corballis [26] have suggested that remembering past events and imagining future ones require a processing space where information is temporarily maintained and manipulated (i.e.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, damage to prefrontal cortex typically affects cognitive control and monitoring of memory retrieval (Burgess & Shallice, 1996;Simons & Spiers). There is evidence from healthy (D'Argembeau, Ortoleva, Jumentier & Van der Linden,, 2010;Cole, Morrison & Conway, 2013) and brain-damaged individuals (Berryhill, Picasso, Arnold et al, 2010;de Vito, Gamboz, Brandimonte et al, 2012) that executive function also has a role in EFT. In a study of individuals with Parkinsons disease, patients produced future events with reduced episodic detail, especially when novel event constructions were required (de Vito et al, 2012).…”
Section: Discussionmentioning
confidence: 99%